Efektivitas Teknik Sosiodrama untuk Meningkatkan Percaya Diri Siswa - Fahrurrozi, Ryan (Guidance : Jurnal Bimbingan dan Konseling, 2025)
The purpose of this study was to determine how well sociodrama techniques work to improve the self-confidence students. A key component of adolescent psychological development, self-confidence influences social interactions, academic performance, and classroom flexibility. Sociodrama techniques, a learning approach through social roles that allows students to express themselves and understand others' perspectives, are one way to help students gain self-confidence. With a single-group pretest-posttest experimental design, this study employed a quantitative methodology. A self-confidence scale questionnaire, administered before and after therapy (pretest and posttest), served as the primary research tool. To find significant differences between the two groups, statistical tests were used to examine the data. The results showed that the self-confidence of junior high school students was improved by the efficient implementation of sociodrama techniques in guidance service.